Siyāsah Al Manāhij Al Waṭaniyyah: 1968 wa 1975 fii Ta’liim Al lugah Al ‘Arabiyyah - Muzadi, Narul Hasyim (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2024)
In the century 20, Indonesia experienced major changes in politics, economy, and society, which greatly affected the national education system. Under the New Order, education was seen as a strategic tool for achieving national goals, including economic development and political stability. The 1968 curriculum was born after the G30S/PKI uprising, focusing on promoting national ideology and developing practical skills, reflecting the emphasis on the values of the Five Principles. Five years later, the 1975 curriculum was introduced to synchronize education with developments in science and technology, and the needs of dynamic development. This curriculum is more student-centered, with an emphasis on critical thinking and problem-solving skills. In learning Arabic, the 1968 curriculum focuses on acquiring the basics of the language, while the 1975 curriculum p